The effects of dual task gait and balance training in Parkinson's disease: a systematic review - De Freitas, Tatiana Beline; Leite, Paulo Henrique Wong; Doná, Flávia; Pompeu, José Eduardo; Swarowsky, Alessandra; Torriani-Pasin, Camila (Physiotherapy theory and practice, 2020)
In patients with Parkinson's disease (PD), the ability to perform simultaneous tasks may be impaired. However, there is no consensus as to whether the strategy of use dual task (DT) should be used with PD patients during gait and balance training because DT can increase the risk of falls. Therefore, it is necessary to critically analyze the relevant studies and evaluate the indications for the use of DT and its effects as a therapeutic strategy. The aim of this systematic review was to explore the effects of DT gait and balance training in individuals with PD. A total of 602 studies were found. After applying the eligibility criteria, seven studies were selected (three clinical trials, one uncontrolled clinical trial, and three pilot studies). Despite the poor methodological quality, the studies indicated the use of DT during gait and balance training may be beneficial for people with mild to moderate PD in compare of single-task or no intervention. The use of DT during training presented benefits related to gait (gait speed, step length and cadence) and balance (mediolateral and anteroposterior balance in closed-eyes tests). The current scenario shows that using DT in the training seems not to be harmful and could be part of the rehabilitation of PD patients. Further clinical trials are needed to confirm the findings, and it would be the most importance that these studies stratify individuals with degrees of disease severity to verify the effect of using the DT during training.